2002
DOI: 10.1117/12.469311
|View full text |Cite
|
Sign up to set email alerts
|

Imaging caries lesions and lesion progression with polarization-sensitive optical coherence tomography

Abstract: New diagnostic tools are needed for the characterization of dental caries in the early stages of development. If carious lesions are detected early enough, they can be arrested without the need for surgical intervention. The objective of this study was to demonstrate that polarization sensitive optical coherence tomography (PS-OCT) can be used for the imaging of early caries lesions and for the monitoring of lesion progression over time. High-resolution polarization resolved images were acquired of natural car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0
8

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 38 publications
3
58
0
8
Order By: Relevance
“…Near‐infrared OCTs are generally used for biological tissues because light in that spectral region undergoes minimal absorption and moderate scattering, allowing imaging with micrometric resolution to a depth of 3 mm, typically . The OCT technique has been successfully applied to the diagnosis of dental caries due to changes in the optical properties of enamel after undergoing demineralization . Images obtained by OCT can be evaluated qualitatively by identification of structures, dimensions, and proportions , and quantitatively, for example by analyzing the reflectivity or the total optical attenuation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Near‐infrared OCTs are generally used for biological tissues because light in that spectral region undergoes minimal absorption and moderate scattering, allowing imaging with micrometric resolution to a depth of 3 mm, typically . The OCT technique has been successfully applied to the diagnosis of dental caries due to changes in the optical properties of enamel after undergoing demineralization . Images obtained by OCT can be evaluated qualitatively by identification of structures, dimensions, and proportions , and quantitatively, for example by analyzing the reflectivity or the total optical attenuation .…”
Section: Introductionmentioning
confidence: 99%
“…The OCT technique has been successfully applied to the diagnosis of dental caries due to changes in the optical properties of enamel after undergoing demineralization . Images obtained by OCT can be evaluated qualitatively by identification of structures, dimensions, and proportions , and quantitatively, for example by analyzing the reflectivity or the total optical attenuation . Using OCT, it has been demonstrated in several studies that demineralized enamel shows stronger optical backscattering , and different authors have extensively studied the characteristics and the dynamic of the remineralization of enamel, for teeth submitted to different periods of pH cycling .…”
Section: Introductionmentioning
confidence: 99%
“…The PS‐OCT system is completely controlled using Labview software (National Instruments, Austin, TX). The system is described in greater detail . Acquired scans are compiled into b‐scan files.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that polarization sensitive optical coherence tomography (PS‐OCT) can nondestructively measure the severity of subsurface demineralization in enamel and dentin and is therefore well suited for this role . Early in vitro studies of the use of OCT for monitoring tooth demineralization demonstrated that OCT can be used to measure the loss of enamel due to exposure to a demineralizing solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation